Characterization of Genetic Variability and Population Structure of the Tick Amblyomma aureolatum (Acari: Ixodidae). Issue 4 (26th May 2016) - Ogrzewalska, Maria; Schwarcz, Kaiser; Bajay, Miklos M.; Bajay, Stephanie K.; Pinheiro, José B.; Zucchi, Maria I.; Pinter, Adriano; Labruna, Marcelo B.
Abstract: The hard tick Amblyomma aureolatum (Pallas) is a vector of the bacterium Rickettsia rickettsii, the etiologic agent of Brazilian spotted fever (BSF) in parts of Brazil. Despite its wide distribution in southeastern South America and its public health importance, there is no information about genetic variation of this species that might help to understand the epidemiology of BSF. Using data from eight microsatellite markers and ticks from six localities, we used a population genetics approach to test the hypothesis that tick populations from areas with the presence of R. rickettsii are genetically different from ticks from areas without R. rickettsii . Contrary to expectations, we found low genetic structure between studied regions. Thus, the presence of R. rickettsii in the specific area is more likely correlated with ecological and the environmental conditions or due to unknown gene coding regions of A. aureolatum genome that would be related to R. rickettsii infection resistance.